Origin and spread of Bos taurus: new clues from mitochondrial genomes belonging to haplogroup T1. - Silvia Bonfiglio; Catarina Ginja; Anna De Gaetano; Alessandro Achilli; Anna Olivieri; Licia Colli; Kassahun Tesfaye; Saif Hassan Agha; Luis T Gama; Federica Cattonaro; M Cecilia T Penedo; Paolo Ajmone-Marsan; et al. (PLoS ONE, 2012)
BACKGROUND: Most genetic studies on modern cattle have established a common origin for all taurine breeds in the Near East, during the Neolithic transition about 10 thousand years (ka) ago. Yet, the possibility of independent and/or secondary domestication events is still debated and is fostered by the finding of rare mitochondrial DNA (mtDNA) haplogroups like P, Q and R. Haplogroup T1, because of its geographic distribution, has been the subject of several investigations pointing to a possible independent domestication event in Africa and suggesting a genetic contribution of African cattle to the formation of Iberian and Creole cattle. Whole mitochondrial genome sequence analysis, with its proven effectiveness in improving the resolution of phylogeographic studies, is the most appropriate tool to investigate the origin and structure of haplogroup T1. METHODOLOGY: A survey of >2200 bovine mtDNA control regions representing 28 breeds (15 European, 10 African, 3 American) identified 281 subjects belonging to haplogroup T1. Fifty-four were selected for whole mtDNA genome sequencing, and combined with ten T1 complete sequences from previous studies into the most detailed T1 phylogenetic tree available to date. CONCLUSIONS: Phylogenetic analysis of the 64 T1 mitochondrial complete genomes revealed six distinct sub-haplogroups (T1a-T1f). Our data support the overall scenario of a Near Eastern origin of the T1 sub-haplogroups from as much as eight founding T1 haplotypes. However, the possibility that one sub-haplogroup (T1d) arose in North Africa, in domesticated stocks, shortly after their arrival from the Near East, can not be ruled out. Finally, the previously identified "African-derived American" (AA) haplotype turned out to be a sub-clade of T1c (T1c1a1). This haplotype was found here for the first time in Africa (Egypt), indicating that it probably originated in North Africa, reached the Iberian Peninsula and sailed to America, with the first European settlers.